Valoração ambiental: síntese dos principais métodos - Ribeiro, Gregório Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
This study aims to show some methods of environmental assets valuation. These methods are intended to assist in the economic value estimation to environmental resources by the simulation of a hypothetical market, even if there are no market prices related to them. It is about an individual preference measure against the environmental changes. Thus, the environmental valuation methods do not convert a natural resource into a market product. The present report evaluates the applicability of the valuation methods to determine the economic value for assets or resources. The challenge for all is to understand the current economic and ecologic thinking and their limitations, so as to seek improvements in the perception of natural phenomena and in the economic-oriented goal, which is the sustainable development.

O presente trabalho tem o objetivo de apresentar alguns dos principais métodos de valoração de bens naturais. Estes métodos auxiliam na estimativa de valor econômico aos recursos ambientais, utilizando a simulação de mercados hipotéticos, mesmo que não existam preços de mercado relacionados ao bem. Trata-se de mensurar as preferências de indivíduos frente a alterações sofridas pelo meio ambiente. Portanto, os métodos de valoração ambiental não transformam um recurso natural em um produto de mercado. O presente estudo avaliou a capacidade dos métodos de valoração para atribuir o valor monetário dos bens e serviços ambientais. O desafio está em compreender as correntes de pensamentos econômicos e ecológicos, além de suas limitações na busca de melhorias na percepção dos ciclos naturais e fenômenos econômicos visando o desenvolvimento sustentável.
Keywords: Engenharia ambiental; Desenvolvimento sustentável; Metodologias de valoração; Economic environmental valuation; Valuation methods; Sustainable development